PROFIL PENJUAL JAGUNG BAKAR (Studi Sektor Informal Pada Malam Hari di Jalan Air Hitam Kota Pekanbaru) - Simbolon, Risky Martiana Br; Yusuf, Yusmar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research was conducted at Jalan Air Hitam Pekanbaru City with the aim of obtaining information about Corn Seller Profile . Problems to be studied is as follows (1) How does the outpouring of family labor in the sale of corn? (2) How does the social relationships in a corn merchant activity? The title of this research is